Time to Castration Resistance as a Predictor of Response to Docetaxel in Metastatic Castration Resistance in Prostate Cancer - İlkay Gültürk; Gülçin Şahingöz Erdal; Gülru Birce Sönmezoz; Mesut Yılmaz; Seher Yıldız Tacar; Aykut Özmen; Deniz Tataroğlu Özyükseler; Özgecan Dulgar; İbrahim Çil; Deniz Tural (İstanbul Medical Journal, 2022)

(untitled)
Introduction:For metastatic prostate cancer (PC), androgen deprivation therapy (ADT) is the primary treatment option. Most patients develop resistance, after an initial response to treatment. This study aimed to evaluate real-life data of first-line docetaxel treatment for metastatic castration-resistant prostate cancer (mCRPC) and analyzed whether the response time to ADT could predict the response to docetaxel treatment.Methods:The study included 111 patients with mCRPC who were treated with docetaxel. Time to castration resistance (TTCR) was defined as the time from initiation to the failure of primary ADT. Patients were divided into two groups based on TTCR. Patients with TTCR ≤12 months were assigned to group 1, while patients with TTCR >12 months were assigned to group 2.Results:The median overall survival (OS) of the patients in group 1 was 16 months, whereas the median OS in group 2 was 38 months. Group 2 had a statistically significantly longer OS than group 1 (p<0.001). The median progression-free survival (PFS) of the patients in group 2 was 14 months while the median PFS in group 1 was 7 months. Group 2 had a statistically significantly longer PFS than group 1 (p<0.001). TTCR, Gleason score, and liver metastasis parameters were found to be predictive factors for OS.Conclusion:In patients with mCRPC, TTCR was found to be a predictor of OS and PFS who were treated with docetaxel.